2017
DOI: 10.1002/pds.4257
|View full text |Cite
|
Sign up to set email alerts
|

Changes in misuse and abuse of prescription opioids following implementation of Extended‐Release and Long‐Acting Opioid Analgesic Risk Evaluation and Mitigation Strategy

Abstract: While similar decreases were observed for the IR prescription opioid group, the decreasing rate for the ER/LA opioids exceeded the decreasing rates for the IR prescription opioids and was distinctly different than that for the prescription stimulants, indicating that the ER/LA REMS program may have had an additional effect on decreases in opioid abuse and intentional misuse beyond secular trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…22 Some REMS programs for opioids appear to have decreased intentional misuse of the drugs and raised awareness and appreciation of their risks. 23,24 Of course, it is not always possible to determine whether changes to prescribing or consumption patterns are based on REMS, other factors, 24 or a combination. 25 In the case of opioids, to-date REMS activities cannot be unequivocally linked to lower mortality.…”
Section: Is There a Role For Rems?mentioning
confidence: 99%
See 1 more Smart Citation
“…22 Some REMS programs for opioids appear to have decreased intentional misuse of the drugs and raised awareness and appreciation of their risks. 23,24 Of course, it is not always possible to determine whether changes to prescribing or consumption patterns are based on REMS, other factors, 24 or a combination. 25 In the case of opioids, to-date REMS activities cannot be unequivocally linked to lower mortality.…”
Section: Is There a Role For Rems?mentioning
confidence: 99%
“…There have been benefits for REMS opioid programs: 46 states in the United States plus the District of Columbia now mandate some form of continuing education for opioid prescribing 22 . Some REMS programs for opioids appear to have decreased intentional misuse of the drugs and raised awareness and appreciation of their risks 23,24 . Of course, it is not always possible to determine whether changes to prescribing or consumption patterns are based on REMS, other factors, 24 or a combination 25 .…”
Section: Commentmentioning
confidence: 99%
“…The legislative authority of FDA allows it to require the conduct of REMS, but not to require postmarketing studies, from license holders of generic products. Key components of the Opioid Analgesic REMS are to make education available to prescribers and the health-care team through accredited continuing education (CE), to provide patient educational materials, and assess the impact of such activities on health outcomes [29][30][31]. In addition to the class-wide opioid PMR studies, companies that are license holders of abuse deterrent opioids are required to conduct separate postmarketing studies to evaluate abuse deterrence in real-world use.…”
Section: Overview Of Study Planmentioning
confidence: 99%
“…Prior assessments of the ER/LA REMS have been funded by opioid manufacturers and identified declines in ER/LA misuse. However, these declines were self-reported by clinicians and reflected population-level trends rather than direct comparisons of CE completers and noncompleters. Pre-post analyses by CE providers, which were also funded by manufacturers, suggested that CE completers had moderately greater ER/LA knowledge immediately after and 2 months after CE training.…”
Section: Introductionmentioning
confidence: 99%